Implanted Dental Pulp Cells Fail to Induce Regeneration in Partial Pulpotomies. (November 2017) - Mangione, F.; EzEldeen, M.; Bardet, C.; Lesieur, J.; Bonneau, M.; Decup, F.; Salmon, B.; Jacobs, R.; Chaussain, C.; Opsahl-Vital, S.
Cell-based partial pulp regeneration is one of the promising approaches to obtain newly formed functional dentin-pulp complex. It relies on the preservation of the healthy tissue while regenerating the damaged pulp. The aim of this study was to investigate whether this regenerative process could be achieved by implanting porcine dental pulp cells (pDPCs) in pulp defects in the minipig. By split-mouth model, self-assembling injectable nanopeptide hydrogel, with and without pDPCs, was implanted after cameral pulpotomy in premolars and molars. At day 21 after surgery, 3-dimensional morphometric characterization, Masson's trichrome staining, and immunolabeling for DSP and BSP (dentin sialoprotein and bone sialoprotein) were performed on treated teeth. This study demonstrated no pulp regeneration but systematic reparative dentinogenesis. In fact, regardless of the presence of pDPCs in the scaffold, an osteodentin bridge—the microarchitecture of which significantly differed from the native dentin—was systematically obtained. Furthermore, the presence of pDPCs significantly affected the microstructure of the dentin bridges. In the radicular area of each treated tooth, hyperemia in the remaining pulp and external root resorptions were observed. Under the conditions tested in this work, pulp regeneration was not achieved, which highlights the need of further investigations to develop favorable regenerative microenvironment.